2009
DOI: 10.1371/journal.pmed.1000201
|View full text |Cite
|
Sign up to set email alerts
|

Blood Glucose and Risk of Incident and Fatal Cancer in the Metabolic Syndrome and Cancer Project (Me-Can): Analysis of Six Prospective Cohorts

Abstract: Tanja Stocks and colleagues carry out an analysis of six European cohorts and confirm that abnormal glucose metabolism is linked with increased risk of cancer overall and at specific sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
179
4
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(195 citation statements)
references
References 42 publications
10
179
4
2
Order By: Relevance
“…Although biologically plausible, results from epidemiological studies are conflicting. The "hyperglycemia hypothesis" is supported by large inception cohort studies that demonstrate a strong relationship between elevated blood glucose and cancer incidence or mortality (24,(29)(30)(31). However, a recent meta-analysis reported a nonsignificant pooled risk ratio for cancer incidence of 0.91 (95% CI 0.79-1.05) for subjects with improved glycemic control across three trials, compared with those in the control arms of the studies, suggesting that improved glycemic control does not confer a reduced risk of cancer among diabetic patients (32).…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…Although biologically plausible, results from epidemiological studies are conflicting. The "hyperglycemia hypothesis" is supported by large inception cohort studies that demonstrate a strong relationship between elevated blood glucose and cancer incidence or mortality (24,(29)(30)(31). However, a recent meta-analysis reported a nonsignificant pooled risk ratio for cancer incidence of 0.91 (95% CI 0.79-1.05) for subjects with improved glycemic control across three trials, compared with those in the control arms of the studies, suggesting that improved glycemic control does not confer a reduced risk of cancer among diabetic patients (32).…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…Several postulated DM-related mechanisms of carcinogenesis, including hyperglycemia itself and/or decreased bioactivity of insulin such as hyperinsulinemia or insulin resistance, have been controversial. 27,28 A meta-analysis of several prospective studies reported that not only higher levels of insulin and C-peptide but also higher levels of blood glucose significantly increased the risk of pancreatic and colorectal cancers. 29 But this meta-analysis had a critical limitation, in that few studies took fasting status into account.…”
Section: Discussionmentioning
confidence: 99%
“…26 Stocks et al showed that the elevated blood levels of glucose were linked with increased cancer risk. 27 Yeh et al demonstrated that glucose and glycolysis-related genes participated in tumorigenesis of human colorectal cancers. 28 The levels of intermediates of glucose metabolism (citrate and lactate) were markedly lowered in serum samples from BC patients compared with those from healthy subjects, which might account for the accumulation of glucose observed in this study.…”
Section: Glucose Metabolismmentioning
confidence: 99%